Applied communication research methods : getting started as a researcher - Boyle, Michael P., 1975-; Schmierbach, Mike, 1976- (2024)
"This third edition is again a practical introduction to communication research methods, foregrounding the role research plays in communication and media industry careers. Covering major methodologies such as surveys, experiments, focus groups, in-depth interviews, content analysis, and others, the book takes the reader through the research process from beginning to end. The text continues to help students link the research methods they learn to practical contexts through its activities and features, which include Voices from Industry boxes written by practitioners that give insight into application of methods; Steps to Success research review checklists; and numerous end-of-chapter activities to reinforce concepts. This third edition contains updates throughout, including an expanded discussion of reliability and validity across both qualitative and quantitative research contexts as well as new Research in Action boxes that showcase how research is used in professional and public contexts. The text is ideally suited to both undergraduate and graduate courses in communication research methods within communication, media, and mass communication programs. Online resources, including sample syllabi, PowerPoint slides, and test banks are available at www.routledge.com/9781032288819"--
Basic principles of research and a guide to using this book -- Basic concepts of research -- Scholarly research and the creation of knowledge -- Ethical research -- Concept explication and measurement -- Sampling -- Effective measurement -- Validity -- Studying people quantitatively -- Studying people qualitatively -- Analyzing texts and other artifacts -- Reliability and subjectivity -- Descriptive statistics -- Estimation and inference -- Bivariate and multivariate statistics.
Includes bibliographical references and index.
Keywords: Communication -- Research; Communication -- Methodology